SISTEM MONITORING KETERSEDIAAN BARANG BERBASIS WEB MENGGUNAKAN METODE FIRST IN FIRST OUT (STUDI KASUS: STAND MAKANAN LONG POTATO WISATA VILLA KHAYANGAN BOGOR) - Daffa Al Ghifary (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The Long Potato Food Stall located in the Villa Khayangan Tourism Area, Bogor, still manages its raw material inventory manually, resulting in difficulties in stock monitoring, accumulation of older materials, and an increased risk of material deterioration. This study aims to design and develop a web-based inventory management system by implementing the First In First Out (FIFO) method to ensure that raw materials are utilized according to their order of arrival. The research employed the prototype development method, which consists of analysis, design, implementation, and testing phases. The results indicate that the developed system is capable of managing incoming and outgoing inventory data, providing real-time stock information, and assisting the business owner in controlling inventory more effectively. Furthermore, the implementation of the FIFO method helps reduce the risk of raw material damage and improves inventory management efficiency. Therefore, the proposed system supports smoother business operations and enhances the accuracy of raw material inventory control, contributing to more effective and efficient inventory management.